A room-temperature interfacial approach towards iron/nitrogen co-doped fibrous porous carbons as electrocatalysts for the oxygen reduction reaction and Zn–Air batteries. Issue 21 (21st May 2019) - Lu, Chenbao; Zhang, Jichao; Chen, Zhenying; Jiang, Kaiyue; Li, Mingqiang; Zhang, Fan; Tong, Gangsheng; Zou, Xiaoxin; Su, Yuezeng; Zhuang, Xiaodong
Abstract : The development of nonprecious and efficient catalysts to boost the oxygen reduction reaction (ORR) is imperative. Abstract : The development of nonprecious and efficient catalysts to boost the oxygen reduction reaction (ORR) is imperative. However, the majority of previously reported approaches suffered from a complicated fabrication procedure, both time consuming and difficult to scale up. Herein, large-scale iron ion embedded polyaniline fibers were successfully fabricated as precursors for preparing iron/nitrogen co-doped fibrous porous carbons (Fe/NPCFs) through an interfacial engineering strategy at room temperature. As ORR electrocatalysts in an alkaline medium (0.1 M KOH), Fe/NPCFs display a positive half-wave potential of 0.827 V ( vs . RHE), and high limited current density (up to 5.76 mA cm −2 ), which are better than those of commercial Pt/C ( E 1/2 = 0.815 V, J L = 5.47 mA cm −2 ). Also, Fe/NPCFs exhibit a high ORR catalysis activity ( E 1/2 = 0.632 V, J L = 5.07 mA cm −2 ) in acidic medium (0.5 M H2 SO4 ). When used as an air cathode in a primary Zn–air battery, high power density (158.5 mW cm −2 ) and specific capacity (717.8 mA h g −1 ) can be easily achieved, outperforming the commercial Pt/C.